4CPS-036 Apremilast adherence in patients with psoriasis and psoriatic arthritis. (March 2019) - Fernández-Sala, X; González-Colominas, E; Navarrete Rouco, E; Ferrández, O; Carballo, N; Gonzalez, R; Tarrasón, L; Beltrán, E; Gallardo, F; Ferran, M; Grau, S
Abstract : Background: A limited number of studies have evaluated medication adherence in psoriasis (PS) or psoriatic arthritis (PsA), reporting rates between 29% and 88% (medication possession ratio (MPR >80%)). However, until now no study has included apremilast as the evaluated drug. Purpose: To evaluate adherence to apremilast treatment in patients with PsO and PsA, and to assess the possible factors associated with a MPR <100%. Material and methods: Retrospective observational study including all patients beginning apremilast in an outpatient pharmacy service from a tertiary university hospital. Exclusion criteria: patients with less than one medication pharmacy refill (early discontinuation or recent treatment initiation). Data collected: demographics, treatment indication, previous biological treatment, incidence of adverse events (AE) and adherence to apremilast using the MPR. Differences between patients with a MPR ≥100% vs. MPR <100% were evaluated in the univariate analysis. Results: Forty-one patients were included: 47 (23–68) years; male 56.1%; PsA 70.7%; and previous biologic therapy 26.8%. At least one adverse effect was reported in nine (21.9%) patients. Thirteen (31.7%) patients discontinued apremilast because of none-response, three (7.3%) for adverse events and one (2.4%) for loss of follow-up. Adherence was: MPR 100% in 22 (53.7%), MPR 90%–99% in 11 (26.8%), MPR 80%–89% in four (9.8%), MPR 70%–79% in two (4.9%) and MPR <70% in two (4.9%) patients. Conclusion: Apremilast adherence rate was >90% in more than 80% of the patients. Considering MPR >80% reported in the literature, this rate was achieved in approximately 90% of patients, probably related to a multidisciplinary attention. The none factor was associated with a poorer adherence, however further studies including a greater number of patients are required. References and/or acknowledgements: No conflict of interest.